**Solve the inequality. 2(4x – 3) ≥ –3(3x) + 5x? x ≥ 0.5 x ≥ 2 (–∞, 0.5]**

2(4x - 3) > = -3(3x) + 5x

8x - 6 > = -9x + 5x

8x - 6 > = - 4x

-6 > = -4x - 8x

-6 > = - 12x

-6/-12 < = x

0.5 < = x or x > = 0.5 <==

** if u multiply/divide by a negative, the inequality sign changes

**Answer:**

**Step-by-step explanation:**

Given the inequality:

**Applying the distributive property on the left hand side : **

we have then;

or

then, following steps to be followed as:

1) Group variable terms on the left side of the inequality

2) Group constant terms on the right side of the inequality

3) Add the variable terms

4) Add the constant terms , then

5) find the value of x

add 6 on both sides we get,

**Simplify:**

Add 4x on both sides we get,

On simplify we get,

⇒ or

If your question is not fully disclosed, then try using the search on the site and find other answers on the subject Mathematics.

Find another answersMathematics, published 11.05.2023

Mathematics, published 23.03.2023

Use the equation to identify the center and radius of the circle (X+3)^2+(y-7^2=11

Mathematics, published 27.05.2023